Religious Moderation as a Strategy to Counter Radicalization: A Study of Islamic Education Students at Indonesia Higher Education - Ahmad Fahri Yahya Ainuri; Mustafakamal Waeduereh; Faldin Fahza Alfaizi; Farhanna Aulia Rahmah; Farkhah Fatimatul Zahro (Journal of Islamic Education Thought and Development, 2026)
This study aims to analyze the implementation of religious moderation as an effort to overcome radicalization among Islamic Religious Education (PAI) students of UIN Walisongo Semarang. This research uses a descriptive qualitative method. This approach was chosen to describe and analyze the phenomenon of the implementation of religious moderation as an effort to overcome radicalization among Islamic Religious Education (PAI) students of UIN Walisongo Semarang in depth which is designed to explore students' understanding of religious moderation and radicalism. The results showed that most students had a fairly good understanding of the concepts of radicalism (54%) and religious moderation (60%). The majority of respondents (65%) consider religious moderation to be very important in preventing radicalism in the educational environment, while the level of radicalization among students is considered low by (55%) respondents. This research makes a significant contribution to the development of inclusive Islamic Education in higher education. Theoretically, this research enriches the scientific treasures of Islamic education by integrating the concept of religious moderation as a preventive step against radicalism, while strengthening the conceptual foundation for the development of a nationalistic PAI curriculum. Practically, the findings of this research can be used as a reference for lecturers, PAI study program managers, and higher education policy makers in designing learning strategies that are able to fortify students from the influence of radicalism, so as to create a generation of religious educators who are moderate, tolerant, and contribute positively to the harmony of national and religious life.